Mavrilimumab, a human monoclonal antibody targeting GM-CSF receptor-α, in subjects with rheumatoid arthritis: a randomised, double-blind, placebo-controlled, phase I, first-in-human study. Issue 9 (25th May 2011) - Burmester, Gerd R; Feist, Eugen; Sleeman, Matthew A; Wang, Bing; White, Barbara; Magrini, Fabio
Abstract : Objective: To evaluate the safety, tolerability, pharmacokinetic and pharmacodynamic profiles of mavrilimumab, a human monoclonal antibody targeting the granulocyte-macrophage colony-stimulating factor receptor-α, in subjects with rheumatoid arthritis (RA). Methods: A randomised, double-blind, placebo-controlled, dose-escalating phase I study in subjects with RA who received stable methotrexate treatment for ≥3 months before enrolment. Subjects received single intravenous escalating doses of mavrilimumab (0.01–10.0 mg/kg) or placebo. Results: 32 subjects were enrolled in this study (1 unblinded subject at 0.01 mg/kg and another at 0.03 mg/kg were followed by five sequential double-blinded cohorts, n=6 each, treated with 0.1, 0.3, 1.0, 3.0 and 10.0 mg/kg, respectively). Adverse events were mild or moderate and were reported with similar frequency across all treatment cohorts. One subject (10.0 mg/kg) experienced moderate face and neck urticaria during infusion that resolved with symptomatic treatment. Systemic clearance of mavrilimumab approached that of endogenous IgG at doses >1.0 mg/kg; pharmacodynamic activity was confirmed in the 1.0 and 3.0 mg/kg cohorts by suppression of suppressor of cytokine signalling 3 mRNA transcripts. In exploratory analyses, reductions of acute phase reactants were observed in subjects with elevated C-reactive protein (>5 mg/l) and erythrocyte sedimentation rate (≥20.0 mm/h) at baseline. No significant change in Disease Activity Score 28-joint assessment (DAS28) was seen in any of the cohorts. In mavrilimumab-treated subjects (n=15) with baseline DAS28 >3.2, mean disease activity (DAS28) was significantly reduced at 4 weeks. Conclusion: In this first-in-human study, mavrilimumab showed preliminary evidence of pharmacodynamic activity. Importantly, the safety and pharmacokinetic profiles of mavrilimumab support further clinical studies in RA. Trial registration number: NCT00771420 .